Sound Production of English Dental Fricatives by Papuan EFL Students - Wira Kafryawan; Zulihi Zulihi (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2023)
This study aims to reveal to what extent Papuan EFL students correctly produce English dental fricatives and to find out what consonants substitute voiceless dental fricative /θ/ and voiced dental fricative /ð/ when misarticulation occurs. A descriptive analysis of 30 native Papuan EFL students was taken as the participants of the study. Data were collected by giving pronunciation tests and targets of either voiceless dental fricative /θ/ or voiced dental fricative /ð/ in an onset or coda syllable position. Correct sound production of English dental fricatives, both voiceless and voiced dental fricatives, by Papuan EFL students hardly found and almost unrecognized that only 12.0% of Papuan EFL students correctly pronounce voiceless dental fricative /θ/ and only 3.3% of Papuan EFL students correctly pronounce voiced dental fricative /ð/. It can be stated that the sound production of English dental fricatives lies in low-level production. Furthermore, Papuan EFL students mostly substitute voiceless dental fricative /θ/ with voiceless alveolar plosive /t/ indicated by 84.0% sound substitution. In other words, Papuan L1 speakers dominantly substitute the consonant /θ/ with the consonant /t/. Papuan EFL students frequently substitute voiced dental fricative /ð/ with both voiced alveolar plosive /d/ indicated by 51.6%, and voiceless alveolar plosive /t/ indicated by 43.3% substitution. Thus, Papuan L1 speakers primarily replace the consonant /ð/ with both consonant /d/ and /t/. The implications for the EFL teaching and learning process may assist Papuan EFL students in learning the correct pronunciation of English dental fricatives in order to improve their speaking proficiency